Turnover Intention and Perceived Organizational Support; Mediating Role of Work Engagement and Organizational Commitment - Nadeem, Kashif; Khan, Muhamamd Ahsan; Imtiaz, Ms. Nazish; Iftikhar, Yasir (European Scientific Journal, ESJ, 2019)
The purpose of this research is to address practical issues regarding the prediction and prevention of turnover intentions of highly skilled employees by focusing on Perceived Organizational Support and two of its outcomes i.e. Organizational Commitment and Work Engagement. Data was collected from different banks of Lahore i.e; Bank of Punjab, Habib Bank Ltd., Meezan Bank, Alfalah Bank, Standard Chartered, UBL, and MCB were visited. This cross-sectional study has used a quantitative technique in order to collect data from a sample size of 300 respondents. In this study, item response theory is used to select the sample size. To collect the data, the questionnaires were distributed among bankers. The response rate was 93% (i.e. 280 out of 300). Results show that Perceived Organizational support has a high impact on turnover intention whereas the organizational commitment and work engagement both can support the Perceived organizational support. Whereas if Perceived organizational support is increased with the help of Organizational Commitment and Work Engagement there will be less turn over intentions in the Organization.